Type VI Aplasia Cutis Congenita: Bart's Syndrome - Ferit Kulalı; Ahmet Yagmur Bas; Yusuf Kale; Istemi Han Celik; Nihal Demirel; Sema Apaydın (Hindawi Limited, 2015)
Bart's syndrome is characterized by aplasia cutis congenita and epidermolysis bullosa. We present the case of a newborn male who developed blisters on the mucous membranes and the skin following congenital localized absence of skin. Bart's syndrome (BS) is diagnosed clinically based on the disorder's unique signs and symptoms but histologic evaluation of the skin can help to confirm the final diagnosis. The patient was managed conservatively with topical antibacterial ointment and wet gauze dressing. Periodic follow-up examinations showed complete healing. We emphasized that it is important to use relatively simple methods for optimal healing without the need for complex surgical interventions.